Evaluation of morphological and psychological outcomes after sub-brow blepharoplasty - Wang, Tengfei; Li, Yunke; Pang, Mengru (Frontiers in Surgery, 2025)
PurposePeriorbital aging commonly presents with upper eyelid laxity and brow descent. Sub-brow blepharoplasty is a promising surgical intervention to address these concerns. This study aimed to evaluate both morphological and psychological outcomes of sub-brow blepharoplasty in a Chinese population.MethodsSixty-four patients undergoing sub-brow blepharoplasty at the Plastic Surgery Department of Guizhou Medical University (January 2022–October 2023) were enrolled. All surgeries were performed by the same surgeon. Standardized follow-ups occurred postoperatively at T1 (immediately), T2 (1 month), and T3 (6 months), with preoperative evaluation at T0. Morphological changes were assessed through standardized photography, measuring brow, eyelid, and canthal positions. Psychological outcomes were assessed using the Social Appearance Anxiety Scale (SAAS). Patient satisfaction was recorded at final follow-up.ResultsOf the 64 patients, 49 (98 eyes) completed all follow-ups (mean follow-up: 7.5 months; follow-up rate: 76.56%). Significant improvements were observed in all morphological indices and SAAS scores postoperatively (P < 0.05). No postoperative complications occurred. At final follow-up, 71.43% of patients were extremely satisfied, 22.45% satisfied, and 6.12% neutral—yielding a 93.88% overall satisfaction rate.ConclusionSub-brow blepharoplasty significantly improves eyebrow position, facial aesthetics, and reduces social appearance anxiety with high patient satisfaction and minimal risk.